Auxiliary liver transplants: technical aspects - Sanguinetti, Julio; Chifflet, Juan; Maglione, Hugo; Fernández, Miguel A; Beguiristain, Alberto; del Campo, Alberto (Cirugía del Uruguay, 1973)
Experimental work on technical aspects of auxiliary liver transplants comprises technique for donor's hepatectomy and for hypothermal perfusion of liver. Graft is invariably placed on right iliac fossa; there are, however; variants in vascular connections. The one that proved most satisfactory is anastomosis of recipient's right iliac artery tQ an aortic cylinder of graft. Cava-aava terminolateral anastomosis and mesenterir- porta termino-terminal anastomosis are performed. Drainage of biliary tract is external for prolonged survival of animals used in the experimental work is not one of its aimes.